2011
DOI: 10.2478/s11534-010-0145-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and electric properties of (Fe, Co)/(Si, Ge) multilayers

Abstract: We review selected results concerning the interlayer exchange coupling in Fe/SixFe1−x , Fe/Ge and Co/Si layered structures. Among the ferromagnet/semiconductor systems, Fe/Si structures are the most popular owing to their strong antiferromagnetic interlayer coupling. We show that such interaction depends not only on semiconducting sublayer thickness, but also on deposition techniques and on the chemical composition of the sublayer as well. In similar heterostructures e.g. Fe/Ge, antiferromagnetic coupling was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…The Fe/Si multilayer system has been of particular interest owing to its applications in microelectronics and magnetism. 8 The soft x-ray fluorescence measurements on the Fe/Si multilayer performed previously suggest that a strong interdiffusion between Fe and Si layers gives rise to a silicide layer at the interface. 9 Fe 3 Si, FeSi, and FeSi 2 silicides have been reported to be formed at the interfaces depending upon the thickness and deposition conditions of the constituting Fe and Si layers.…”
Section: Introductionmentioning
confidence: 94%
“…The Fe/Si multilayer system has been of particular interest owing to its applications in microelectronics and magnetism. 8 The soft x-ray fluorescence measurements on the Fe/Si multilayer performed previously suggest that a strong interdiffusion between Fe and Si layers gives rise to a silicide layer at the interface. 9 Fe 3 Si, FeSi, and FeSi 2 silicides have been reported to be formed at the interfaces depending upon the thickness and deposition conditions of the constituting Fe and Si layers.…”
Section: Introductionmentioning
confidence: 94%
“…The aim of this work is to clear up the role of nonmagnetic interlayer material in forming of inner structure and magnetic properties of multilayer granular films. Previously it was found that in multilayer systems composed of continuous metallic magnetic layers (Fe, Co) and interlayers of semiconductors (Si, Ge), provided the thickness of interlayer was less than 2-4 nm, it was possible to observe both antiferromagnetic exchange interaction and ferromagnetic one [1,2]. For good insulators the interlayer exchange coupling has never been observed experimentally even for very thin interlayers [2].…”
Section: Introductionmentioning
confidence: 99%
“…Previously it was found that in multilayer systems composed of continuous metallic magnetic layers (Fe, Co) and interlayers of semiconductors (Si, Ge), provided the thickness of interlayer was less than 2-4 nm, it was possible to observe both antiferromagnetic exchange interaction and ferromagnetic one [1,2]. For good insulators the interlayer exchange coupling has never been observed experimentally even for very thin interlayers [2]. The properties of granular multilayer systems based on CoFeZr, CoFeB alloys in Al 2 O 3 and SiO 2 matrix with nonmagnetic interlayers have been studied in [3][4][5].…”
Section: Introductionmentioning
confidence: 99%